2020
DOI: 10.2174/1874467212666191113130312
|View full text |Cite
|
Sign up to set email alerts
|

FAT10: Function and Relationship with Cancer

Abstract: Posttranslational protein modifications are known to be extensively involved in cancer, and a growing number of studies have revealed that the ubiquitin-like modifier FAT10 is directly involved in cancer development. FAT10 was found to be highly upregulated in various cancer types, such as glioma, hepatocellular carcinoma, breast cancer and gastrointestinal cancer. Protein FAT10ylation and interactions with FAT10 lead to the functional change of proteins, including proteasomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…This enzyme has been shown to influence many cellular processes, including cell cycle regulation [ 20 ]. In recent, the influence of FAT10 on the malignant tumours is investigated extensively [ 34 ], while other studies reported that the FAT10 is participated in renal disease pathogenesis [ 22 , 23 ]. However, there is currently no information on the impact of FAT10 on the renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme has been shown to influence many cellular processes, including cell cycle regulation [ 20 ]. In recent, the influence of FAT10 on the malignant tumours is investigated extensively [ 34 ], while other studies reported that the FAT10 is participated in renal disease pathogenesis [ 22 , 23 ]. However, there is currently no information on the impact of FAT10 on the renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…HLA‐F adjacent transcript 10 (FAT10) is a member of the ubiquitin‐like protein family and is also known as ubiquitin D (Xiang et al, 2019). Studies have shown that FAT10 may arrest the cell cycle at the G1‐phase and lead to inhibition of apoptosis (Yi et al, 2020).…”
Section: Involvement Of the Hippo Pathway In Osmentioning
confidence: 99%
“… 8 Deregulation of UBD may result in aberrant modifications in apoptosis, cell division, or chromosomal instability, all of which are linked to cancer. 9 Increased studies on UBD in malignancies have emerged in recent years, revealing a link between increased UBD expression and disease development in several tumors, 10 , 11 such as hepatocellular carcinoma, 12 , 13 colon cancer, 14 gastric cancer, 15 oral squamous cell carcinoma, 16 breast cancer, 17 and glioma. 18 However, the role of UBD in rectal cancer had never been explored.…”
Section: Introductionmentioning
confidence: 99%